2014
DOI: 10.1016/j.toxlet.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity but not the AhR-mediated activity of PAHs is inhibited by other components of complex mixtures of ambient air pollutants

Abstract: In this study, we compared the genotoxicity and aryl hydrocarbon receptor (AhR)-dependent transcriptional changes of selected target genes in human lung epithelial A549 cells incubated for 24 h, either with extractable organic matter (EOMs) from airborne particles <2.5 μm (PM2.5) collected at four localities from heavily polluted areas of the Czech Republic or two representative toxic polycyclic aromatic hydrocarbons (PAHs) present in EOMs, benzo[a]pyrene (B[a]P) and benzo[k]fluoranthene (B[k]F). Genotoxic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…In our previous studies, we have focused on comparison of genotoxic dose-responses (determined as DNA adduct formation) with induction of AhR activation in A549 cells [7] and global gene expression in human lung fibroblasts HEL cells treated with the same set of EOM samples [6]. Here, we attempted to identify gene expression changes induced in human alveolar carcinoma A549 cells by a complex mixture of air pollutants adsorbed on PM2.5, and to compare the effects of EOMs originating from distinct localities and sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we have focused on comparison of genotoxic dose-responses (determined as DNA adduct formation) with induction of AhR activation in A549 cells [7] and global gene expression in human lung fibroblasts HEL cells treated with the same set of EOM samples [6]. Here, we attempted to identify gene expression changes induced in human alveolar carcinoma A549 cells by a complex mixture of air pollutants adsorbed on PM2.5, and to compare the effects of EOMs originating from distinct localities and sources.…”
Section: Discussionmentioning
confidence: 99%
“…In this study numerous biological processes and signaling pathways have been found to be deregulated in response to various organic extracts from PM2.5, and the key role of the activated AhR has been identified. In a follow-up study, performed in human lung epithelial adenocarcinoma cells A549, we have further observed that EOM-induced DNA adduct levels are relatively low, as compared to levels induced by similar concentrations of benzo[a]pyrene (B[a]P) [7]. We suggested that this might be due to competitive inhibitory effects of some non-genotoxic EOM components requiring identical enzymatic activities for their metabolism as genotoxic PAHs, which are mostly responsible for DNA adduct formation by EOM [8].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Human lung cell lines are routinely used to assess the toxicities of PM and mixture of ambient air pollutants (Deng et al, 2014;Líbalová et al, 2014;Michael et al, 2013;Yu et al, 2015). However, effects of exposure to a combination of Pb, a typical air pollutant, and silica, a typical UFP, are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is the reason that the colour of the samples can disturb results of spectrophotometer reading at wavelength 340 nm. Described problem is not presented in publications conducted by other authors on A549 cell line, but the testing procedure in this cases is different from PAN-I instruction [12][13][14].…”
Section: Discussionmentioning
confidence: 99%